Ultrasonographic characteristics of accessory sex glands and spectral Doppler indices of the internal iliac arteries in peri-and post-pubertal Dorper rams raised in a subtropical climate - Camela, E. S. C. [UNESP] (2017)
The aim of the present study was to determine and compare ultrasonographic characteristics of accessory sex glands and spectral Doppler indices of the internal iliac arteries in peri- and postpubertal rams raised in a subtropical climate. Forty-five Dorper rams were examined (24 rams aged 8-11 months and 21 rams aged 12-24 months). Digital images of all accessory sex glands were subjected to morphometric and echotextural analyses, the latter using commercially available image analytical software Image ProPlue. Physical and morphological characteristics of semen and serum concentrations of testosterone were also determined. The dimensions of the prostate gland (12.9 +/- 1.2 compared with 14.2 +/- 2.7 mm; mean standard deviation) and bulbourethral glands (13.7 +/- 1.3 compared with 14.7 +/- 1.8 ram) were greater (P = 0.04) in sexually mature compared with peri-pubertal rams. Pixel intensity of vesicular (181.5 +/- 20.8 compared with 164.8 +/- 26.8, P = 0.02) and bulbourethral gland parenchyma (166.9 +/- 16.9 compared with 141.8 +/- 29.1, P = 0.001) was greater in peri-pubertal compared with sexually mature rams. Semen could be collected by ejaculation into the artificial vagina from 38% (8/21) of post-pubertal rams and 21% (5/24) of peri-pubertal animals (P = 0.03). Semen volume was positively cOrrelated with peak systolic velocity (PSV) and end-diastolic velocity (EDV) in the internal iliac arteries (r = 0.79, P = 0.001 and r = 0.67, P = 0.01, respectively), while spermatic vigor and progressive motility were inversely related to circulating concentrations of testosterone (r = 0.69) P = 0.009 and r = 0.61, P = 0.03, respectively). In summary, the attainment of sexual maturity in the rams of the present study was associated with an enlargement of the prostate and bulbourethral glands, and with the shift in echotextural attributes of vesicular and bulbourethral glands. Circulating testosterone concentrations and Doppler blood flow indices of the ram's internal iliac arteries are significant predictors of sperm progressive motility, vigor and the amount of ejaculate.